As dimensões da prática cotidiana dos assistentes sociais nos Centros de Atenção Psicossocial – CAPS I da 8º Regional de Saúde do Estado do Paraná sob a ótica dos parâmetros para atuação de assistentes sociais na saúde - Berti, Luciani Aparecida (2021)
The CAPS are configured from the 1990s as a new socio-occupational space in the area of mental health for the social worker, being considered one of the main devices of the mental health policy. Faced with advances in the sphere of health and mental health, the Social Worker is also recognized as a health professional, capable of giving answers to the expressions of the social question in this field, but his performance is permeated by difficulties and also possibilities. In view of the reflection presented, the present study aims to understand and analyze the daily practice of social workers inserted in the Psychosocial Care Centers-CAPS I of the 8th Regional Health of Paraná from the perspective of the document entitled: Parameters for the performance of social workers in health, prepared by the Federal Council of Social Service-CFESS. Therefore, in a limited way, the research problem is expressed in the following question: How are the Parameters for the Action of Social Workers in the health policy in the Psychosocial Care Centers-CAPS I materialized? To answer this question, a semi-structured questionnaire was applied, consisting of nineteen questions, conducted from a script with objective and subjective questions, with the instrument being made available on the Google Forms platform, considering the Covid-19 pandemic scenario and aiming to understand and to analyze the daily practice of social workers inserted in these spaces from the perspective of the document entitled “Parameters for the performance of Social Workers in Health”. As a methodological procedure, a qualitative approach was chosen from the perspective of Marxist theory. O universe researched includes social workers inserted in CAPS I of the 8th Regional Health of Paraná State It is concluded that most professionals say that institutional limits are characterized as one of the main difficulties. It was not possible to state that professionals use the Parameters document in their daily lives, but they have other important theoretical references, such as the Code of Ethics and the Law of Regulation of the Profession, in addition to regulations such as the Organize Health Law and Law nº 10,216 redirects mental health care. In this way, thinking about the work of the social worker in these spaces proposes us to think about the political and social conjunctural issues that make up Brazilian society today and that permeate professional practice. Therefore, despite the limitations inherent to the research, the study allowed an approximation with the daily practice of these professionals, highlighting the main difficulties experienced, seeking to contribute to the recognition of Social Work as a Health profession and its possibilities of action.